The Relationship between Anti-Mullerian Hormone Level and the Severity of Systemic Lupus Erythematosus in Women at Reproductive Age - Maryam Mousavi; Bahram Pakzad; Zahra Seyedbonakdar; Mehdi Khajehazad (مجله دانشکده پزشکی اصفهان, 2019)
Background: Systemic lupus erythematosus (SLE) is a common autoimmune disease, and if not diagnosed and treated in a timely manner, can lead to irreversible complications such as lupus nephritis. Thus, the early detection of the disease is very important. On the other hand, some studies have shown that there is a relationship between the serum levels of anti-Mullerian hormone (AMH) and the activity of lupus disease. The aim of this study was to determine the relationship between antibody titer with severity and activity level of SLE.